Platelet-Rich Fibrin in Coverage of Gingival Recession: A Systematic Review and Meta-Analysis - Rodas, Miguel Augusto Riquelme; Paula, Bruna Luísa de; Pazmiño, Victor Fabrizio Cabrera; Lot Vieira, Flávia Ferraz dos Santos; Junior, Joel Ferreira Santiago; Silveira, Elcia Maria Varize (European Journal of Dentistry, 2020)
This systematic review and meta-analysis sought to evaluate the efficacy of platelet-rich fibrin (PRF) membranes versus subepithelial connective tissue grafts (SCTGs) in the coverage of Miller class I and II gingival recessions. After the inclusion and exclusion criteria were applied, the quality of seven articles (Cohen’s Kappa = 0.9) was evaluated using the Jadad scale. The MEDLINE/PubMed, Cochrane, and Web of Science databases were consulted, and manual searches were performed in the most popular periodontics journals. The studies included considered a total of 122 patients, 203 surgical fields on which SCTGs were used, and 205 surgical fields on which PRF was used. The parameters analyzed were probing depth, clinical attachment level, gingival recession, and keratinized mucosa. The minimum follow-up period accepted was 6 months. A statistically significant difference between the SCTG and PRF groups was found only in the case of keratinized mucosa. However, gingival recession, clinical attachment level, and probing depth parameters in the PRF group were found to be statistically equal to those of the SCTG group (the gold standard) (p ≥0.05). PRF membranes were determined to be a promising alternative to autogenous gingival grafts in the treatment of Miller class I and II gingival recessions.
Keywords: connective tissue; platelet-rich fibrin; gingival recession; systematic review